An Adult Case of Adenovirus-Associated Acute Disseminated Encephalomyelitis - Dewayne Campbell; Gordon S. Wong; Hyun Park; Gavin McLeod (Case Reports in Infectious Diseases)
Acute disseminated encephalomyelitis (ADEM) is an autoimmune neurological disease that predominately affects pediatric population. Only a single fatal adult case of adenovirus-associated ADEM has previously been published by Qamar et al. in 2021. Here, we present an adult case of adenovirus-associated ADEM, which was diagnosed early in her clinical course. The patient was treated with the prompt initiation of steroids, intravenous immune globulin (IVIG), and plasmapheresis (PLEX), and the patient recovered fully. This case highlights the importance of early accurate diagnosis for other clinicians to treat adenovirus-associated ADEM in a timely fashion to prevent a potentially fatal outcome.